Can Christianity and modernity go together? - Lenaers, Roger (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2015)
Looking at the question “Can Christianity and modernity go together?” at first glance the answer is no. It has been observed that where modernity grows, to the same extent does religion, nevertheless, the Christian faith is decreasing. The reason is that modern science which developed in Europe has shown since the Enlightenment the certainty that natural phenomena are not the result of divine intervention, but are explained perfectly well by natural causes. Thus discovering the autonomy of the universe and of man, modernity began to walk away from religion, since it is essentially the belief in a Theos, a supernatural being from whom everything would depend, which denies autonomy. So the Christian faith could not enter modernity to save it, although this is its mission. Fortunately Christianity is not by nature a religion: it has become one. By nature it is a faith in Jesus and God, as Jesus experienced it and lived. We cannot free ourselves from all religions, but we can free ourselves from the image of a Theos in order to meet the Absolute Reality which is Absolute Love. The article develops in detail what this demands from us.